MARKETING AND PROMOTION STRATEGIES IN VISITING INTEREST BACK TO JUNGELAND ADVENTURE THEME PARK SENTUL - Eviana Tarigan; Liliana Dewi (Jurnal Inovasi Penelitian, 2022)
Jungleland adventure theme park tour is one of the most popular tours in the city of Bogor. Initially, the Covid-19 pandemic situation made this tourist attraction closed and almost unkempt. But at the beginning of 2022, Jungeland reopened, of course, it is very difficult for jungleland to make confidence back in tourists to want to visit. Of course, promotional media is a benchmark to recreate tourist interest. In this study, researchers tried to examine exactly what management can do in making tourists interested in coming back. Promotional media and marketing are certainly the most important things in order to attract tourists.